Innovation as mediator between entrepreneurial orientation and spin-off venture performance. (2nd November 2010) - Helm, Roland; Mauroner, Oliver; Dowling, Michael
A fundamental challenge in entrepreneurship is how to predict firm performance particularly for high technology sectors. In previous empirical research on high technology ventures the concepts of entrepreneurial orientation and entrepreneurial behaviour have been found to be able to differentiate between successful and unsuccessful entrepreneurs. The aim of this paper is to discuss why entrepreneurial orientation and in particular risk taking behaviour and proactivity is of particular importance in the context of high-technology venture success. Furthermore, we argue that innovativeness as a central entrepreneurial object mediates between the motivation and the success of entrepreneurs. Therefore we assume a mediation model between motivation, innovativeness and success. Regarding this model the entrepreneurial orientation of the founders influences new venture performance through its generation of innovativeness. To test the mediation we analyse data from 165 high technology spin-off companies in Germany with structural equation modelling. The results suggest that especially in high technology sectors and in fast growing markets, such as biotechnology, healthcare, information technology and optics where innovation is necessary to endure a pronounced entrepreneurial orientation is important.